Pharmacological properties and underlying mechanisms of curcumin and prospects in medicinal potential - Yaw-Syan Fu (Biomedicine & Pharmacotherapy, 2021)
Curcumin, isolated from Curcuma longa L., is a fat-soluble natural compound that can be obtained from ginger plant tuber roots, which accumulative evidences have demonstrated that it can resist viral and microbial infection and has anti-tumor, reduction of blood lipid and blood glucose, antioxidant and removal of free radicals, and is active against numerous disorders various chronic diseases including cardiovascular, pulmonary, neurological and autoimmune diseases. In this article is highlighted the recent evidence of curcuminoids applied in sevral aspects of medical problem particular in COVID-19 pandemics. We have searched several literature databases including MEDLINE (PubMed), EMBASE, the Web of Science, Cochrane Library, Google Scholar, and the ClinicalTrials.gov website via using curcumin and medicinal properties as a keyword. All studies published from the time when the database was established to May 2021 was retrieved. This review article summarizes the growing confirmation for the mechanisms related to curcumin's physiological and pharmacological effects with related target proteins interaction via molecular docking. The purpose is to provide deeper insight and understandings of curcumin's medicinal value in the discovery and development of new drugs. Curcumin could be used in the prevention or therapy of cardiovascular disease, respiratory diseases, cancer, neurodegeneration, infection, and inflammation based on cellular biochemical, physiological regulation, infection suppression and immunomodulation.